The ERP signature of the contextual diversity effect in visual word recognition - Vergara-Martínez, Marta (2017)
Behavioral experiments have revealed that words appearing in many different contexts are responded to faster than words that appear in few contexts. Although this contextual diversity (CD) effect has been found to be stronger than the word-frequency (WF) effect, it is a matter of debate whether the facilitative effects of CD and WF reflect the same underlying mechanisms. The analysis of the electrophysiological correlates of CD may shed some light on this issue. This experiment is the first to examine the ERPs to high- and low-CD words when WF is controlled for. Results revealed that while high-CD words produced faster responses than low-CD words, their ERPs showed larger negativities (225-325 ms) than low-CD words. This result goes in the opposite direction of the ERP WF effect (high-frequency words elicit smaller N400 amplitudes than low-frequency words). The direction and scalp distribution of the CD effect resembled the ERP effects associated with "semantic richness." Thus, while apparently related, CD and WF originate from different sources during the access of lexical-semantic representations.